GREEN SUPPLY CHAIN: MODEL ERP UNTUK KOPERASI KECIL DALAM MENGURANGI BIAYA OPERASIONAL - Tanjung, Riani; Rahmawati, Ariska Yuni; Anti, Desak Made Sri Geby (Universitas Logistik dan Bisnis Internasional, 2024)
A cooperative is an economic entity that is unique, namely ownership and purpose business involving members. In cooperatives, apart from being a business owner, members at the same time become perpetrators or actors in operating the business. Cooperatives are business entities that collectively achieve the goals of the individuals who are members. The small farming industry, despite the second food and drink production, often faces many challenges in managing their product. KPSBU as provider credit of small farming industry members has scheduled the delivery chain. This abstract introduces the concept of a Green Supply Chain tied to the specific needs of small-scale credit providers in a small farming sector. By examining the potential benefits and addressing the challenges faced by these farmers to reduce such costs which caused by their activity, this study aims to shed light on practical strategies for developing cost-effective and environmentally sustainable supply chain practices in the context of small-scale corps called the ERP model. Through case studies and analyses, this research provides insights that can empower small farmers to navigate the intersection of economic viability and environmental stewardship by adapting and comparing the cost with the efficiency of maximum output.